Specific and Sensitive RP-HPLC Method Development and Validation for the Determination of Aripiprazole: Application in Preformulation Screening of Nanoemulsion - Kumbhar, Santosh A.; Kokare, Chandrakant R.; Shrivastava, Birendra; Choudhury, Hira (Current Nanomedicine, 2020)
Background: It has been hypothesized that delivery of aripiprazole through nanoemulsion formulation would better deliver the drug into the central nervous system to treat major depressive conditions in psychological patients. Due course of formulation development, to determine solubility of the drug in different matrices and nanoemulsion is an important step. Materials & Methods: Therefore, a simple, rapid and selective reversed phase high performance liquid chromatographic (RP-HPLC) method was developed and validated for the determination of aripiprazole as per International Conference of Harmonization (ICH) guidelines. Satisfactory analysis method was employed for the quantitative determination of aripiprazole during pre-formulation development. Results and Discussion: The separation technique was achieved using the mobile phases of methanol-acetonitrile, 80:20 (v/v) delivered at 1.0 mL.min-1 flow rate through HIQ SIL C18 250x4.6 mm (5 μm particle size) column and detected at 218 nm wavelength. The method depicted linear calibration plots within the range of 5 to 50 μg.mL-1 with a determination coefficient (r2) of 0.9991 calculated by least square regression method. The validated method was sensitive with LOD of 10.0 ng.mL-1 and 30.0 ng.mL-1 of LOQ. The intra-day and inter-day precision values were ranged between 0.37-0.89 and 0.63-1.11 respectively, with accuracy ranging from 98.24 to 100.88 and 97.03 to 100.88, respectively. This developed and validated method was found to be sensitive for the determination of aripiprazole for the first time from various oils, surfactants, co-surfactants, and nanoemulsion formulation. Conclusion: This RP-HPLC method was successfully implemented for the quantitative determination of aripiprazole at developmental stages of nanoemulsion formulation.
Keywords: surfactants